PERSONNEL SUPPORT FOR THE SOCIO-ECONOMIC SECURITY OF AN ENTERPRISE - MATIUKH, Serhii; KORBUT, Sergiy; HAYDUK, Olena; RUDNICHENKO, Yevhenii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the role of personnel support in the economic security system of an enterprise, emphasizing its importance in protecting businesses from various threats and risks. The main components of the economic security system are analyzed, highlighting the interaction of personnel support with other elements that form a comprehensive security management system. Particular attention is paid to personnel policy as a strategic direction of human resource management, defining the key principles and approaches to working with employees, as well as the factors influencing its formation.The article presents a personnel support model that includes key components such as goals, tasks, functions, and principles of personnel management to ensure economic security. The functions of personnel support are outlined, including risk assessment, personnel strategy development, employee supervision, security training, staff motivation, conflict investigation, confidential information management, and psychological state monitoring.It is noted that effective personnel support helps to reduce risks associated with the human factor and is a crucial element in ensuring enterprise stability and security. The article emphasizes the importance of the interconnection between personnel support and personnel policy in achieving the strategic goals of an enterprise and maintaining its competitiveness.
Keywords: security; economic security of an enterprise; economic security system; personnel support; personnel policy